2010
DOI: 10.1111/j.1523-5378.2010.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Association Between Helicobacter pylori Infection and Anemia Age Dependent?

Abstract: H. pylori infection is associated with higher prevalence of anemia in school-age children independently of socioeconomic variables. Such association was not observed in infants. These findings are of clinical and public health importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
7
34
0
3
Order By: Relevance
“…In adult T1DM patients, autoimmune gastritis is characterized by gastric atrophy, APCA autoantibodies, achlorydria and hypergastrinemia, iron deficiency anemia, and B 12 deficiency [27], and may predispose to gastric carcinoid tumors [27]. Interestingly, iron deficiency anemia is a common and initial manifestation of autoimmune gastritis [28], but may also result from H. pylori infection [29], as corroborated in 2 of our patients. One of our APCA-positive patients had hypergastrinemia without concomitant H. pylori infection.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In adult T1DM patients, autoimmune gastritis is characterized by gastric atrophy, APCA autoantibodies, achlorydria and hypergastrinemia, iron deficiency anemia, and B 12 deficiency [27], and may predispose to gastric carcinoid tumors [27]. Interestingly, iron deficiency anemia is a common and initial manifestation of autoimmune gastritis [28], but may also result from H. pylori infection [29], as corroborated in 2 of our patients. One of our APCA-positive patients had hypergastrinemia without concomitant H. pylori infection.…”
Section: Discussionmentioning
confidence: 72%
“…As gastric autoimmunity is usually asymptomatic [29], it has been suggested that patients with APCA positivity should be annually investigated with gastrin, ferritin, vitamin B 12 and complete blood count [26]. Should elevated APCA levels and hypergastrinemia be detected, gastroscopy with multiple biopsies should be performed [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Helicobacter pylori has been implicated in several earlier studies as a cause of IDA refractory to oral iron treatment, with a favorable response to H pylori eradication [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…Major population surveys conducted over diverse geographic areas [16][17][18][19][20][21][22][23] indicate that H pylori positivity is associated with an increased prevalence of iron deficiency, and meta-analysis of 19 observational epidemiologic studies and 6 interventional trials revealed an increased risk for IDA with a pooled odds ratio (OR) of 2.8 among H pylori-infected subjects. 24 Meta-analysis of 16 randomized trials involving 956 patients with documented H pylori infection and IDA showed that the increments from baseline to end point in Hb, serum iron, and serum ferritin were significantly higher with anti-H pylori treatment plus oral iron compared with oral iron alone.…”
Section: H Pylori Gastritismentioning
confidence: 99%